Prevalence of ESBL and MBL Producing Escherichia coli among Urinary Tract Infection Patients at Star Hospital - Shrestha, Ram Krishna; Karmacharya, Sanish; Alle Magar, Kiran; Pandit, Suyog; Tyata, Radha; Nepal, Rupa; Thakur, Rajesh Kumar (Nepal Journal of Health Sciences, 2026)
Introduction: Urinary tract infection (UTI) is one of the most common bacterial infections worldwide, with Escherichia coli being the principal causative organism. In recent years, the increasing emergence of multidrug-resistant E. coli has complicated UTI management. The production of extended-spectrum β-lactamases (ESBLs) and metallo-β-lactamases (MBLs) represents a major resistance mechanism, limiting the effectiveness of many commonly used antibiotics. Continuous local surveillance of antimicrobial resistance patterns is therefore essential to guide effective empirical therapy. Objective: This study aimed to determine the prevalence of ESBL- and MBL-producing E. coli among patients with UTIs and to assess the antimicrobial resistance patterns of these isolates. Methods: A total of 300 urine samples from suspected UTI patients attending Star Hospital, Lalitpur, were processed using standard microbiological methods. E. coli isolates were identified, and antimicrobial susceptibility testing was performed using the Kirby–Bauer disc diffusion method in accordance with CLSI guidelines. Multidrug-resistant isolates were screened and confirmed for ESBL and MBL production. Results: Bacterial growth was observed in 220 (73.3%) samples, of which 150 (68.2%) isolates were identified as E. coli. UTIs were more common in females (74.6%) than males (25.4%), with the highest prevalence in the 21–30-year age group (53.3%). High resistance was noted to amoxicillin (85.3%), cefalexin (76%), ceftazidime (74%), cefotaxime (70.6%), and cefixime (70%). Seventy-five (50%) isolates were multidrug-resistant, among which 46% were ESBL producers and 22% were MBL producers. ESBL-producing isolates showed highest susceptibility to tigecycline (95.6%), followed by meropenem (78.2%) and amikacin (68.2%). Conclusions: A high prevalence of ESBL-producing E. coli was observed, with a smaller proportion producing MBL. Routine antimicrobial susceptibility testing, including detection of ESBL and MBL, is essential to guide appropriate therapy and reduce treatment failure.